Daily Behavior of Javan Gibbon (Hylobates moloch) Ragunan Wildlife Park: Implications for Reintroduction and Welfare Assesment: Perilaku Harian Owa Jawa (Hylobates moloch) di Taman Margasatwa Ragunan: Implikasi terhadap Reintroduksi dan Kesejahteraan Satwa di Konservasi Ex-Situ - Gustimaya, Nizarani; Pusparini, Fitria (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
The Javan gibbon (Hylobates moloch) is a primate endemic to Java that has been classified as endangered by the IUCN since 2015. Conservation efforts are carried out through breeding and ex-situ conservation. This study aims to analyze the daily behavior patterns of Javan gibbons at Ragunan Wildlife Park and assess their relationship with animal management, including cage conditions, feed, and enrichment as a basis for recommendations to improve animal welfare. The study was conducted on two male and female individuals using the scan sampling method, focusing on feeding, resting, moving, and social activities. Data analysis was conducted using qualitative-descriptive methods. The results showed that the dominant activity was movement (≥20%), followed by resting (15%), feeding (≥6%), and socializing (≥3%). Activity increased in the afternoon between 2:50 p.m. and 3:00 p.m. This pattern differs from the behavior of gibbons in their natural habitat, which has the potential to reduce their natural abilities and hinder the success of their release. This study provides important empirical data on the behavioral adaptation of Javan gibbons in captivity, which has rarely been studied in the context of ex-situ conservation in Indonesia.